Organic matter pools, C turnover and meiofaunal biodiversity in the sediments of the western Spitsbergen deep continental margin, Svalbard Archipelago. (January 2016) - Pusceddu, A.; Carugati, L.; Gambi, C.; Mienert, J.; Petani, B.; Sanchez-Vidal, A.; Canals, M.; Heussner, S.; Danovaro, R.
Abstract: We investigated organic matter (OM) quantity, nutritional quality and degradation rates, as well as abundance and biodiversity of meiofauna and nematodes along the deep continental margin off Spitsbergen, in the Svalbard Archipelago. Sediment samples were collected in July 2010 and 2011 along a bathymetric gradient between 600 m and 2000 m depth, and total mass flux measured at the same depths from July 2010 to July 2011. In both sampling periods sedimentary OM contents and C degradation rates increased significantly with water depth, whereas OM nutritional quality was generally higher at shallower depths, with the unique exception at 600 m depth in 2010. Meiofaunal abundance and biomass (largely dominated by nematodes) showed the highest values at intermediate depths (ca 1500 m) in both sampling periods. The richness of meiofaunal higher taxa and nematode species richness did not vary significantly with water depth in both sampling periods. We suggest here that patterns in OM quantity, C degradation rates, and meiofauna community composition in 2011 were likely influenced by the intensification of the warm West Spitsbergen Current (WSC). We hypothesize that the intensity of the WSC inflow to the Arctic Ocean could have an important role on benthic biodiversity and functioning of deep-sea Arctic ecosystems. Highlights: Benthic ecosystems were investigated along the Arctic margin in July 2010 and 2011. Organic matter quantity, quality and turnover varied significantly with water depth. Richness of meiofaunal taxa and nematode species did not vary across depths. Local currents could influence the Arctic margin benthic ecosystems.